Transesterification of palm oil with methanol using barium oxide - Muhamad Zahrul, Ghazali (2012)
Transesterification is a transformation of ester into biodiesel accelerated with catalysts.Biodiesel or biofuel is a great solution in greenhouse problems emitted by petroleum diesel.Unlike underground oil reserves,biofuels are a renewable resource since crop can always grow and turn into fuel.Using Barium Oxide as solid catalyst is to counterpart problems by homogenous catalyst which require more energy in washing process for separation which lead to more waste.The present studies aimed to determine the conversion of methyl ester produced and the optimum operation condition for the transesterification process.The research study is done in a batch reactor system.Optimum operating condition is at 50°C with molar ration of palm oil to methanol is 1:15 and with catalyst loading of 3 wt%.The highest conversion of methyl esters from this optimum operating condition is 84.15%.